Pengaruh Manajemen Talenta dan Manajemen Pengetahuan Terhadap Efektivitas Organisasi dan Kinerja Organisasi - Ninik Indrayani; Toni Herlambang; Ni Nyoman Putu Martini (STIE Mandala Jember, 2023)
This study aims to examine the effect of talent management and knowledge management on organizational effectiveness through organizational performance. This research was conducted in April – May 2022. The number of respondents was 100 people. The sampling technique used a questionnaire. The results showed that there was a positive and significant influence of talent management on the organizational performance of the Fatimah Islamic Hospital in Banyuwangi. There is a positive and significant influence of knowledge management on the organizational performance of the Fatimah Islamic Hospital in Banyuwangi. There is a positive and significant influence of talent management on the organizational effectiveness of the Fatimah Islamic Hospital in Banyuwangi. There is a positive and significant influence of knowledge management on the organizational effectiveness of the Fatimah Islamic Hospital in Banyuwangi. There is a positive and significant effect of organizational performance on the organizational effectiveness of the Fatimah Islamic Hospital in Banyuwangi. There is a positive and significant influence of talent management on organizational effectiveness through the organizational performance of the Fatimah Islamic Hospital in Banyuwangi. There is a positive and significant influence of knowledge management on organizational effectiveness through the organizational performance of the Fatimah Islamic Hospital in Banyuwangi.